2024
DOI: 10.1108/lodj-08-2023-0449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of individual-focused transformational leadership on individual work performance: mediating role of work engagement and moderating role of regulatory focus

Panawannage Bhagya Dewmini Fernando,
Ananda K.L. Jayawardana

Abstract: PurposeThis study aims to investigate how the individual-focused transformational leadership effect of transformational leadership impacts the team member’s individual work performance through the intermediary mechanisms of work engagement and regulatory focus.Design/methodology/approachA moderated mediation model was analyzed through PLS-SEM by using a sample of 462 team members across diverse work teams in Sri Lankan organizations.FindingsResults revealed that individual-focused transformational leadership p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…This study provides interesting results. On the one hand, consistent with previous research (Breevaart et al, 2016;Fernando and Jayawardana, 2024;Jiatong et al, 2022;Park et al, Pourbarkhordari et al, 2016), job engagement mediated the effect of transformational leadership on task performance, which supported hypothesis 1. When employees feel that their immediate supervisor is behaving in a transformational style, job engagement and subsequent task performance increase.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study provides interesting results. On the one hand, consistent with previous research (Breevaart et al, 2016;Fernando and Jayawardana, 2024;Jiatong et al, 2022;Park et al, Pourbarkhordari et al, 2016), job engagement mediated the effect of transformational leadership on task performance, which supported hypothesis 1. When employees feel that their immediate supervisor is behaving in a transformational style, job engagement and subsequent task performance increase.…”
Section: Discussionsupporting
confidence: 88%
“…In turn, employees who are psychologically present, attentive, connected and focused on their jobs attaint higher task performance. Results support the role of job engagement as a key mechanism for mediating the impact of social context on employee behaviors (Christian et al, 2011) and reaffirm those of the research undertaken in other industries and contexts on the transformational leadership-job engagement-task performance relationship (Breevaart et al, 2016;Fernando and Jayawardana, 2024;Jiatong et al, 2022;Lai et al, 2020;Park et al, 2022;Pourbarkhordari et al, 2016). In a daily study, Breevaart et al (2014) observed that transformational leadership explained more variance in job engagement than contingent reward.…”
Section: Implications For Theorysupporting
confidence: 77%
See 2 more Smart Citations